Clay coatings formation in tepetates from Texcoco, Mexico - Gutiérrez-Castorena, Ma del Carmen; Ortiz-Solorio, C.A.; Sánchez-Guzmán, P. (Catena (Giessen), 2007)
Tepetates are common in the Mexican highlands, and are classified as fragipan, duripan, pedosediments or saprolite. A common feature is the abundance of clay coatings. Three pedons with red tepetate and grey tepetate were selected at different altitudes and slopes in a small watershed in Texcoco, Mexico. Physical, chemical, mineralogical and micromorphological analyses were carried out in soil, tepetate and separated clay coatings. Clay illuviation and neoformation indexes were calculated using micromorphometric techniques. Red tepetate is composed of basic volcanic glass dust ( andesitic vitric tuff), and has a high clay neoformation and illuviation index. In contrast, grey tepetate is composed of acid volcanic glass ( acid vitric tuff) and only clay neoformation takes place, leading to the formation of a clayey soil. Although all the tepetates were subject to pedogenesis, the intensity and variation of the processes increases on the lower slope and different diagnostic horizons are formed, due to tepetate erosion. The laterally running waters containing suspensions of particles and soluble silica were deposited or precipitated in sediments or tepetates on the lower slopes, giving rise to compound coatings. These processes must be older than 20,000 years. Tepetates from Texcoco present several variants which were recognised since pre-Hispanic times.